The enhancement of anomalous Hall effect by inserting MgO layer in perpendicular anisotropic Pd/Co2MnSi/MgO/Pd films - H. R. Fu; L. Ma; N. Tian; C. Y. You; K. Wang (AIP Advances, 2018)
A systematic study of anomalous Hall effect (AHE) was performed in perpendicular magnetic anisotropic Pd/Co2MnSi(tCMS)/MgO/Pd films. The AHE was significantly intensified by inserting MgO layer, which can be ascribed to the enhancement of spin-orbit coupling and interfacial scattering contribution. Moreover, it was found that the Co and Mn ions were reduced at the interface of Co2MnSi/MgO with annealing process. The stable amount of Mn-O bonding was observed at the Co2MnSi/MgO interface after annealing, implying that the proper Mn-O bonding could be favorable for achieving large AHE.